Tip of the trichome: evolution of acylsugar metabolic diversity in Solanaceae - Fan, Pengxiang (Curr Opin Plant Biol, 2019)
Acylsugars are insecticidal plant specialized metabolites produced in the Solanaceae (nightshade family). Despite having simple constituents, these compounds are unusually structurally diverse. Their structural variations in phylogenetically closely related species enable comparative biochemical approaches to understand acylsugar biosynthesis and pathway diversification. Thus far, varied enzyme classes contributing to their synthesis were characterized in cultivated and wild tomatoes, including from core metabolism – isopropylmalate synthase (Leu) and invertase (carbon) – and a group of evolutionarily related BAHD acyltransferases known as acylsucrose acyltransferases. Gene duplication and neofunctionalization of these enzymes drove acylsugar diversification both within and beyond tomato. The broad set of evolutionary mechanisms underlying acylsugar diversity in Solanaceae make this metabolic network an exemplar for detailed understanding of the evolution of metabolic form and function.